2013
DOI: 10.1166/jnn.2013.7197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ambient Relative Humidity and Solvent Properties on the Electrospinning of Pure Hyaluronic Acid Nanofibers

Abstract: Nanofibers exist ubiquitously in natural extracellular matrix (ECM) of all kinds of human tissues forming hydrated interwoven network. Electrospinning nanotechnology has been proven to be a powerful technique to fabricate controllable nanofibers mimicking the natural ECM structures. Hyaluronic acid (HA), as a critical component of natural ECM, has been widely used in tissue engineering and regenerative medicine. In this study, pure HA nanofibers with average diameter of 33 +/- 5 nm, 59 +/- 12 nm, 79 +/- 12 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…For example, Jou [36] presented multilayer fiber based on polyethylene terephthalate. Polyethylene terephthalate fibers were treated with 60 Co-γ-ray and grafted with acrylic acid, and then were grafted with chitosan via esterification. At last, hyaluronic acid was immobilized onto chitosan-grafting fibers.…”
Section: Wet Spinning Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Jou [36] presented multilayer fiber based on polyethylene terephthalate. Polyethylene terephthalate fibers were treated with 60 Co-γ-ray and grafted with acrylic acid, and then were grafted with chitosan via esterification. At last, hyaluronic acid was immobilized onto chitosan-grafting fibers.…”
Section: Wet Spinning Methodsmentioning
confidence: 99%
“…Yao Shenglian et al [60], apart from solvents properties, highlighted an influence of ambient relative humidity on the electrospinnability of the hyaluronan solutions. A critical value of humidity allowing them to successfully obtain uniform hyaluronan fibers with similar diameters and morphologies was equal to 8%.…”
Section: Electrospinningmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of electrospun nanofibers depend on a number of parameters. These parameters are commonly divided into three categories: solution parameters (such as solution concentration and/or viscosity, solution surface tension, and solution conductivity), process parameters (such as feed rate, applied voltage, and tip to collector distance), and ambient conditions (like ambient temperature and humidity) [34][35][36]. The following will discuss the influential parameters on morphology and diameter of fibers in the process of electrospinning.…”
Section: Critical Parameters Of Electrospinningmentioning
confidence: 99%
“…As RH increased further, droplets started to form with poly(vinyl alcohol), poly(ethylene oxide), poly(vinyl alcohol)/hyaluronic acid, poly(ethylene oxide)/chitosan and polystyrene as evaporation rates lowered [7,9,10]. Yao et al [16] reported that by electrospinning a hyaluronic acid solution above a critical RH value, which is Figure 1: Schematic of the direct-write melt-electrospinning apparatus. The water bath is used to melt a PCL polymer which is extruded onto a moving collector plate via the syringe pump.…”
Section: Introductionmentioning
confidence: 99%